Helen Finch. German-Jewish Life Writing in the Aftermath of the Holocaust: Beyond Testimony. Camden House, 2023. - Sam Grayck (Studies in 20th & 21st Century Literature, 2026)
Review of Helen Finch. German-Jewish Life Writing in the Aftermath of the Holocaust: Beyond Testimony. Camden House, 2023. 230 pp.
Keywords: German literature; testimony; Jewish Literature; German-Jewish Literature